PROTECTION OF DIVERSITY AND LEGAL PLURALISM: A DECOLONIAL PERSPECTIVE (ESMAT Magazine, 2025)
This research employs the deductive method and a bibliographic review to discuss the fundamental right to diversity, based on the theory of legal pluralism. The central hypothesis is that fundamental rights inherently encompass rights often denied to minorities who live differently from the majority. The study proposes the expansion and application of existing norms to protect these diversity rights, addressing the issue of differential legal and social treatment that disadvantages minorities. The research considers legal pluralism as a means to realize the fundamental rights to diversity. Furthermore, it adopts a decolonial perspective to assess the role of the State in protecting diversity and human dignity, advocating for the inclusion of marginalized knowledge and voices.
Keywords: Fundamental Rights; Diversity; Decolonial; Legal Pluralism